2019
DOI: 10.1002/pmrj.12091
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Body Mass Index on the Functional Prognosis of Traumatic Brain Injury Patients

Abstract: Background Although many studies have demonstrated that obesity is correlated with an increased risk of chronic disease, some have reported a paradox by which those in the higher weight categories actually recover better during hospitalization. This study was designed to determine whether this obesity paradox is also reflected in the recovery of patients with traumatic brain injury (TBI) undergoing care in a rehabilitation hospital. Objective To investigate the association between body mass index (BMI) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…A conducted a study on The Effect of Body Mass Index on Functional Outcome of Patients With Knee Replacement the FIM scores at the time of discharge improved from 74-108 for normal weight individuals, for overweight 74-108, obese class 1 69-109, for obese class ii 68-108, for obese class iii 65-108. There is not much difference in scores between the groups (Burke et al, 2019a). The above values are correlating with the present study results.…”
Section: Fim Scoressupporting
confidence: 92%
See 1 more Smart Citation
“…A conducted a study on The Effect of Body Mass Index on Functional Outcome of Patients With Knee Replacement the FIM scores at the time of discharge improved from 74-108 for normal weight individuals, for overweight 74-108, obese class 1 69-109, for obese class ii 68-108, for obese class iii 65-108. There is not much difference in scores between the groups (Burke et al, 2019a). The above values are correlating with the present study results.…”
Section: Fim Scoressupporting
confidence: 92%
“…A study conducted to compare the acute recovery during hospitalisation in both normal and obese patients affected with cardiovascular disease, pulmonary disease, traumatic brain injury, and in those hospitalized for amputation. Acute indings were marginally better but no statistical signi icant recovery was observed during hospitalization of overweight as compared to normal weight patients (Burke et al, 2014(Burke et al, , 2019a.…”
Section: Resultsmentioning
confidence: 83%
“…Based on previous research, BMI does not have a significant relationship with the type and severity of head injury or the prognosis or outcome of head injury. [16,17] In this study, BMI was also not associated with LOS from severe head injury patients.…”
Section: Resultsmentioning
confidence: 43%
“…Data from postacute IRF studies have found similar results for patients with stroke, traumatic brain injury, amputation, and debility. 29 , 30 , 31 , 32 Acute findings of marginally better but not statistically significant recovery during hospitalization of overweight as compared to normal weight patients have been found in patients hospitalized for cardiovascular disease, pulmonary disease, traumatic brain injury, and in those hospitalized for amputation. 29 , 30 , 31 , 32 , 33 Therefore, our findings seem to follow a trend noted by others, that both short- and long-term outcomes of those who are overweight are not sufficiently different from the normal weight to trigger a resistance to treatment.…”
Section: Discussionmentioning
confidence: 99%